Customer Accounting Techniques and Financial Performance of Manufacturing Companies in South-South, Nigeria - Inyang, A. B. (Journal of Science Education and Humanities, 2025)
The main purpose of the study was to examine the extent to which the customer accounting techniques influence financial performance of manufacturing companies in South-South, Nigeria. The study adopted descriptive and inferential survey designs. The population of the study consisted of 105 management staff while the sample size was 83 management staff.Judgemental and convenience sampling techniques were used to select the sample. A researcher developed instrument tagged: “Customer Accounting Techniques and Financial Performance Questionnaire (CATFPQ)” was used to collect data for the study. The structured questionnaire had a validated 15 items in all on five points rating scale. Split half reliability test was used to determine the internal consistency of the instrument. The data collected were analysed using simple regression. R2 was used to answer the research questions and F-statistics was used to test the hypotheses at 0.05 significance. The findings of the study revealed that customer profitability analysis, lifetime customer profitability analysis and valuation of customers as assets techniques influence to a low extent the financial performance of manufacturing companies. The findings further showed that there is a significant influence of customer profitability analysis technique, lifetime customer profitability analysis technique, and valuation of customers as assets techniqueon the financial performance of manufacturing companies in South-South, Nigeria. It is recommended among others that the manufacturing companiesapply the customer profitability analysis technique for the analysis of the revenue streams and service costs related to customers.